ANÁLISE DO DESEMPENHO NEUROPSICOMOTOR EM CRIANÇAS DE 2 A 7 ANOS DE IDADE EM ESCOLAS PÚBLICAS DA REDE MUNICIPAL DE IJUÍ/RS EM 2008 E 2009 - Pretto, Luciana M.; Bonamigo, Elenita C. B.; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo